DISCIPLINARY PRACTICE IN PRISONS. REWARDS AND SANCTIONS THAT MAY BE APPLIED TO PERSONS DEPRIVED OF THEIR LIBERTY - Andrei-Cristian ȘTEFAN (Challenges of the Knowledge Society)
Disciplinary practice in prisons is an essential element of the proper administration of correctional institutions and the maintenance of a safe and orderly environment in these facilities. In this paper, we aim to examine the crucial role of rewards and sanctions within the prison system and how they influence the behaviour of prisoners. Rewards and sanctions play a crucial role in shaping prisoners' behaviour and promoting compliance with institutional rules and norms. The main aim of this study is to assess how these disciplinary tools influence prisoners' behaviour and to examine their effectiveness in reducing delinquent and deviant behaviour in prisons. The findings of this analysis highlight the importance of a balanced approach between rewards and sanctions within the prison system. The right balance between these two aspects is essential for promoting a safe prison environment and facilitating the social reintegration of prisoners. A balanced approach can contribute to improving disciplinary practices in prisons and to the effective management of prisoners' behaviour. This research provides an insight into how rewards and sanctions are used within the prison system and suggests that a balanced approach between them is essential for maintaining order and safety in prisons and promoting the social reintegration of prisoners.